Polish-German or European ‘Memory Crisis’? German Exiles During Their Official Speeches Against the Background of the European Integration Process (Economic and Political Thought, 2012)
The aim of the article is to present the influence of the official speechesmade by the representatives of German exiles and other politicians on thecontemporary relations with the eastern neighbors of Germany, especiallyPoland, in the context of contemporary processes taking place in Europe.The text is mainly based on the analysis of German publications. Analyzingthe fragments of speeches made by the leaders of German compatriots’(Landsmannschaft) associations and politicians representing various politicalparties in that country, the author used a comparative method. The aim oforganizing this kind of undertakings was to maintain the interest in andthe memory of the displaced Germans among the society and politicians.The discussion about the role of the collective memory of the World WarII, started by the displaced Germans, was also part of the debate beforethe so-called eastern enlargement of the European Union in 2004, whichinfluenced the relations between Poland and Germany. The proof of thepolitical character of this discussion is the fact that some of the displacedGermans tried to combine the European integration topic with the problemsleft over from the previous era of relations with the eastern neighbors. Thebest example is the participation of Hans Gert Pöttering, the then Presidentof the European Parliament, in Days of Homeland (Tag der Heimat), whospoke about the issue of damages claims in the contemporary relationsbetween Poland and Germany. The use of historical events in politics alsotook place in the first decade of the 21st century and was an attempt to divertattention from current issues on both sides of the Odra as well as in othercountries of the region.